Ukrainian Narratives about the Outbreak of the War: The Main Themes, Structure and Composition - Labashchuk, Oksana; Harasym, Tetiana; Reshetukha, Tetiana; Majbroda, Katarzyna; Verbovetska, Oksana (Tautosakos darbai, 2024)
The article aims to consider the main themes and structures of autobiographical narratives by the Ukrainian people about the outbreak of the Russian-Ukrainian war. It analyses narratives of life events becoming the elements of storytelling about the beginning of the war. The article focuses mainly on the plot structure of stories about the war’s outbreak, and the narrators’ self-presentation strategies. Folklore tools reveal typical plots of autobiographical narratives about the outbreak of war. The symbolic meanings of oral histories attributed in modern Ukrainian culture to various events, people and things are considered. Methods of structural narratology have proven to be advantageous in this research. Autobiographical narratives concerning the outbreak of the war coincide with the five criteria of the eventfulness level by Wolf Schmid: relevance, unpredictability, persistence, irreversibility and non-iterativity. The predominant motifs under consideration include reports regarding the beginning of the war, leaving one’s home, seeking refuge in shelters, undergoing evacuation, contemplating the causes of the war, predicting the war, and reflecting on the cruel nature of warfare.